Advances in Drugs Targeting Lymphangiogenesis for Preventing Tumor Progression and Metastasis - Wang, Chuqi; Chu, Ming (Frontiers in Oncology, 2022)
Metastasis of cancer cells from the primary tumor to other organs and tissues in the body is the leading cause of death in patients with malignancies. One of the principal ways cancer cells travel is through lymphatic vessels, and tumor invasion into the regional lymph nodes is a hallmark of early metastasis; thus, the formation of especially peritumoral lymphatic vessels is essential for tumor transportation that gives rise to further progression. In the past few decades, tumor-induced lymphangiogenesis has been testified to its tight correlation with lymphatic metastasis and poor clinical outcomes in multiple types of human malignancies, which warrants novel potential therapeutic targets for cancer treatment. As the understanding of underlying molecular mechanisms has grown tremendously over the years, an inexorable march of anti-lymphangiogenic therapy development also aroused terrific interest. As a result, a great number of drugs have entered clinical trials, and some of them exhibited predominant contributions in cancer management. Herein, this review provides an updated summary of the current advances in therapies preventing lymphatic metastasis and discusses the validity of different applications.